2011
DOI: 10.1007/s11207-011-9893-4
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting a CME by Spectroscopic Precursor?

Abstract: Multi-temperature plasma flows resulting from the interaction between a mature active region (AR) inside an equatorial coronal hole (CH) are investigated. Outflow velocities observed by Hinode EIS ranged from a few to 13 km s −1 for three days at the AR's eastern and western edges. However, on the fourth day, velocities intensified up to 20 km s −1 at the AR's western footpoint about six hours prior to a CME. 3D MHD numerical simulations of the observed magnetic configuration of the AR-CH complex showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…The amount of flux canceled is very similar to that found in Yardley et al (2017) despite the difference in methods used to calculate the magnetic flux. This is also consistent with previous studies such as Green et al (2011), Baker et al (2012), and Yardley et al (2016. The AR also rotates clockwise during this period.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…The amount of flux canceled is very similar to that found in Yardley et al (2017) despite the difference in methods used to calculate the magnetic flux. This is also consistent with previous studies such as Green et al (2011), Baker et al (2012), and Yardley et al (2016. The AR also rotates clockwise during this period.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Flux cancellation within the AR can be as large is 10%/day of the total AR flux (Sterling et al, 2010;Baker et al, 2012;Green et al, 2011). The size of the ratio of in-AR cancellation to dispersing flux may be inversely related to the AR size (flux content) being the largest in ephemeral ARs.…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
“…Baker et al (2012) and Sterling et al (2010) studied different regions that both showed that 20% of the flux was lost over just two days and Green et al (2011) tracked an active region from emergence to decay and found that 34% of the active region flux was cancelled along the active region's internal polarity inversion within 3.5 days of the flux emergence ending.…”
Section: Flux Cancellation and Removal Of Flux From The Photospherementioning
confidence: 99%
“…The zoomed map shows an inverse S-channel of low-FIP bias along the main PIL which hosts a filament within the AR where a sigmoid/flux rope is forming and will erupt soon thereafter (Baker et al 2012). The two principal sites of flux cancellation along the PIL, indicated by the red circles in Figure 2, are located in low-FIP bias areas.…”
Section: Resultsmentioning
confidence: 99%
“…The Hinode/EIS Fe xii 195.119Å intensity map (left panel) and S x 264.223Å -Si x 258.375Å (middle and right panels) abundance map are shown in Figure 1. See Baker et al (2012) for a complete account of the AR-CH complex observations and Baker et al (2013) for a description of the method used to construct the abundance map derived from Hinode/EIS spectra.…”
Section: Observationsmentioning
confidence: 99%